A phenomenological study on the factors impacting the sustainability of Nasi Kandar among restaurant owners in Penang / Mohamad Azli Bin Razali … [et al.] - Razali, Mohamad Azli; Zainol, Noorliza; Din, Norrina; Rezo, Khairul Hidayat; Mohd Akhir, Irina; Abdullah, Hasniza (Universiti Teknologi MARA, Sabah, 2024)
This study investigates the sustainability challenges confronting Nasi Kandar eateries in Penang, an integral facet of local culture and economy. It aims to comprehend the factors influencing these establishments' sustainability, spanning economic, socio-cultural, and environmental realms. Employing a qualitative phenomenological approach, 15 purposively selected participants underwent in-depth interviews, with thematic analysis unveiling prevalent themes. The findings underscore the intricate nature of sustainability in Penang's Nasi Kandar scene, emphasizing aspects like cost management, staff training, technology integration, menu flexibility, sustainable practices, policy alignment, and community involvement. The research contributes a conceptual framework for addressing industry challenges, stressing holistic approaches integrating menu adaptability, sustainable practices, policy alignment, and community engagement. Practical implications provide actionable insights for restaurant owners to develop robust strategies. Nevertheless, the study recognizes the necessity for further empirical validation and deeper analysis to refine these strategies. Overall, it furnishes a thorough examination of sustainability hurdles in Penang's Nasi Kandar sector, accompanied by pragmatic measures to fortify long-term viability.